Genetics of bacteria - Srivastava, Sheela (Springer, 2013)
This book covers bacterial genetics and realizes the contribution of these tiny organisms to the growth of biological sciences as a whole and genetics in particular. Offers exhaustive coverage of bacterial genetics, with figures and tables where appropriate